2010
DOI: 10.2166/wst.2010.408
|View full text |Cite
|
Sign up to set email alerts
|

Microbial population dynamics of granular aerobic sequencing batch reactors during start-up and steady state periods

Abstract: This study investigates microbial population dynamics in granular sequencing batch reactors (GSBR). The experimental results of DGGE fingerprint of sludge demonstrated that the microbial community structure of sludge shifted significantly during granulation period and nutrient removal improvement period. After reactor performance and physical characteristics of sludge reached steady state, microbial population of sludge became relatively stable. The high similarity of microbial community structure between co-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…These four genera have earlier been reported in different granular sludge reactors operated for organic carbon and nitrogen removal (Li et al, 2008; Ebrahimi et al, 2010; Liu et al, 2010; Zhao et al, 2013, 2015; Kong et al, 2014; Lv et al, 2014; Cydzik-Kwiatkowska, 2015; Figueroa et al, 2015). Thauera and Zoogloea have been found at both low and high OLRs, between 1 and 15 kg COD m -3 d -1 (Ebrahimi et al, 2010; Zhao et al, 2013; Lv et al, 2014).…”
Section: Resultsmentioning
confidence: 57%
“…These four genera have earlier been reported in different granular sludge reactors operated for organic carbon and nitrogen removal (Li et al, 2008; Ebrahimi et al, 2010; Liu et al, 2010; Zhao et al, 2013, 2015; Kong et al, 2014; Lv et al, 2014; Cydzik-Kwiatkowska, 2015; Figueroa et al, 2015). Thauera and Zoogloea have been found at both low and high OLRs, between 1 and 15 kg COD m -3 d -1 (Ebrahimi et al, 2010; Zhao et al, 2013; Lv et al, 2014).…”
Section: Resultsmentioning
confidence: 57%
“…Aerobic granules are the products of microbes that are responding to external survival pressure, such as short settling time or high shear force exerted on the reactor. During the start-up period of the granular sludge reactor, the radical shifts of microbial community structure are reported [22][23][24]. In addition, Li and Li [25] found the rapid granulation by the selective discharge of slow-settling sludge flocs, while mixed, unselective sludge discharge did not lead to the aerobic granulation.…”
Section: Discussionmentioning
confidence: 99%
“…Weissbrodt et al [16] reported reduced nitrogen removal efficiency due to severe biomass wash-out; the ammonium and nitrogen removal recovered after 40 days (to 77% and 60%, respectively). Liu et al [17] achieved complete ammonium removal after 49 days, while Zhao et al [29] obtained the same after 21 days with simultaneous stepwise decreased settling time and gradually increased COD and N-load. However, the authors did not provide information about the strategy applied for decreasing the settling time.…”
Section: Process Performancementioning
confidence: 97%
“…The subsequent impact of biomass loss is deteriorated nitrogen removal efficiency. Rapid changes in the microbial population have also been documented during start-up [17,18]; however, very few studies have examined the abundance and dynamics of the nitrifying community during granulation [19]. Based on a modeling approach, Su et al [20] suggested that a stepwise decrease of settling time can be an effective method for optimizing biomass discharge during start-up, but their study did not investigate the nutrient removal during granulation.…”
Section: Introductionmentioning
confidence: 99%